Managing locally advanced GIST complicated by perforation: A case report and comprehensive review - Nathaniel Grabill, MD; Mena Louis, DO; Mariah Cawthon, MD; Joseph Conway, MD; James Chambers, MD (Radiology Case Reports, 2024)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract, frequently characterized by mutations in the KIT or PDGFRA genes. This case report details the complex clinical course of a 71-year-old female with a history of HIV and metastatic GIST presenting with acute abdominal symptoms indicative of perforated viscus. Initial imaging revealed a massive pneumoperitoneum and a large abdominal mass, necessitating immediate surgical intervention. The patient underwent multiple surgeries, including bowel resections and colostomy creation, to address the extensive tumor burden and complications. Postoperatively, she required intensive care management, including mechanical ventilation, vasopressor support, and hemodialysis for acute kidney injury. Pathological examination confirmed metastatic GIST with extensive mesenteric and omental involvement. Immunohistochemical staining was positive for CD117 (c-KIT) and DOG-1. Despite aggressive surgical and supportive measures, the patient's condition highlighted the significant challenges in managing advanced GIST with perforation. This case highlights the importance of a multidisciplinary approach, integrating surgical, medical, and intensive care to optimize outcomes. The prognosis of GIST varies widely, with localized tumors having favorable outcomes following resection, while metastatic cases often face a poorer prognosis despite advances in targeted therapies. This case exemplifies the critical need for personalized treatment plans and ongoing research to improve the management and prognosis of GIST patients.